Retrospective of legislation on the acquisition (purchase) of wild animals for the purpose of their maintenance and breeding in semi-free conditions or in captivity - O. Yu. Onishchenko (Law and Safety, 2018)
The purpose of the article is to analyze and thoroughly study the special legal literature and the legal and regulatory framework for the emergence and gradual formation of legislation in the field of obtaining (purchasing) wild animals for the purpose of their maintenance and breeding in semi-free conditions or in captivity.